2008
DOI: 10.1519/jsc.0b013e318181a314
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Static and Ballistic Stretching on Measures of Strength and Power

Abstract: Preactivity stretching is commonly performed by athletes as part of their warm-up routine. However, the most recent literature questions the effectiveness of preactivity stretching. One limitation of this research is that the stretching duration is not realistic for most athletes. Therefore, the purpose of this study was to determine the effects of a practical duration of acute static and ballistic stretching on vertical jump (VJ), lower-extremity power, and quadriceps and hamstring torque. Twenty-four subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 19 publications
6
62
1
5
Order By: Relevance
“…The negative effects of SS on muscle force and muscle force production has previously been reported (1,3,4,6,(10)(11)(12)(13)(14)(15)(16)28). Our study showed that SS at 60 and 300 degrees per second did not affect the PT in the stretched extremity.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The negative effects of SS on muscle force and muscle force production has previously been reported (1,3,4,6,(10)(11)(12)(13)(14)(15)(16)28). Our study showed that SS at 60 and 300 degrees per second did not affect the PT in the stretched extremity.…”
Section: Discussionsupporting
confidence: 70%
“…It is believed that stretching before exercises lowers the risk of injury and increases flexibility (2)(3)(4). An increase in flexibility (increasing the range of motion of joints) is expected to improve performance and lower the risk of injury during sports activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both Bacurau and colleagues (2009) and used 20 min of ballistic stretch activities and reported a 2.2% decrease in leg press 1-RM and a ϳ5%-7% decrease in knee flexion and extension 1-RMs, respectively (likely fatigue related). Other studies imposing shorter durations of ballistic stretching or bobbing actions at end ROM have reported no significant effects (Bradley et al 2007;Samuel et al 2008). Cumulatively, the data show a tendency toward an increase in performance with faster and/or more intense ballistic stretches, but substantial variability exists among studies and with regard to performances in different tests within studies, so a firm conclusion cannot be drawn.…”
Section: Effect Of Ds Movement Frequencymentioning
confidence: 73%
“…Behm and Chaouachi (2011) reported a DS doseresponse effect in which greater overall peak force and power improvements were observed when >90 s (7.3% ± 5.3%) vs. <90 s (0.5% ± 2.3%) of DS was imposed immediately before testing. However, trivial ES or statistically nonsignificant performance changes were also elicited by both longer DS durations of 10 min (Needham et al 2009) and 15 min (Zourdos et al 2012) and by 180 repetitions , as well as by shorter durations, such as 45 s (Beedle et al 2008), 60 s (Samuel et al 2008), and 150 s (Amiri-Khorasani et al 2010), or 2 repetitions of 4 exercises (Dalrymple et al 2010). Hence, based on the variability among studies, it is difficult to demonstrate a dose-response relationship with DS.…”
Section: Dose-response Relationship For Dsmentioning
confidence: 95%